Government Policies in Egypt and Indonesia to Mitigate Carbon Emissions: A Comparative Study - Oraby, Ghada Abd Elsattar Mohammed; Orabi, Amira Abd Elsattar Mohamed (PT. Pubsains Nur Cendekia, 2025)
Accelerating global climate change and increasing pressure to fulfill commitments under the Paris Agreement have positioned the effectiveness of national carbon mitigation policies as a critical policy issue for developing countries. This review article compares carbon mitigation policies in Egypt and Indonesia, both of which face similar challenges but operate within different governance contexts. The study employs a descriptive comparative analysis based on a systematic review of national climate strategies, legal frameworks, renewable energy policies, sustainable transport initiatives, private sector engagement, and climate finance mechanisms. Both countries have achieved significant policy progress; however, the effectiveness of carbon mitigation remains constrained by governance challenges, particularly policy coordination, bureaucratic efficiency, and implementation capacity. This study argues that a hybrid policy approach combining Egypt’s regulatory strengths with Indonesia’s long-term planning framework has the potential to enhance carbon mitigation effectiveness. These findings provide policy-relevant implications for other developing countries seeking to strengthen climate governance and accelerate progress toward global emission reduction targets.